Scheduled Tribe Students in Schools of Odisha An Analysis through Statistical Spectacles - Padhi, Sambit Kumar (JOURNAL OF INDIAN EDUCATION, 2016)
Tribes comprise approximately 8.6 per cent of the total population of the country, which probably has the largest number of tribal communities in the world. India, being a classic homeland of Scheduled Tribes, offers a sound human laboratory for conducting a number of researches. The diverse issues of Scheduled Tribes, in general, and their educational development in particular, received wide attention among researchers for a long time because time has shown that education is an inevitable force for the holistic development of people and nation. Odisha occupies a prominent space on the tribal map of India as it consists of a variety of Scheduled Tribe communities. The greatest challenge before the state is to mainstream the socially excluded group like Scheduled Tribe population. A close analysis reveals that literacy and enrolment of tribal children are quite low and considerably lower than the other categories. An attempt has been taken in the first part of this paper to study the sex ratio, overall literacy and gender gap in the literacy rate of Scheduled Tribe population of Odisha. The second part highlights the school education status of Scheduled Tribe children in terms of enrolment, gross enrolment ratio, gender parity index and dropout rate at various levels. Some points have been given in the last part of this paper in order to overcome the upcoming challenges.